Molecular Screening Of Citrate And Structurally Similar Compounds For Prevention Of Lung Tissue Destruction - HEENA SHAH,; PUSHPARANI MUDALIYAR,; CHANDRASHEKHAR KULKARNI, (International Journal of Pharma and Bio Sciences, 2012)
The major function of α1-antitrypsin is to protect the lung against the enzyme neutrophil elastase, which breaks down the connective tissue fibre elastin. However the aggregation of antitrypsin into polymers is one of the causes of neonatal hepatitis, cirrhosis, and emphysema. One possible therapeutic strategy involves inhibiting the conformational changes involved in antitrypsin aggregation by using citrate ion, which has been shown to maintain the protein in an active conformation. In our study we identified compounds structurally similar to citrate and carried out docking of citrate ligand as well as the structurally similar ligands with alpha 1 antitrypsin. From the docking and the dynamics results we conclude that citrate and structurally similar compounds to that of citrate were potent inhibitors which can thus prevent aggregation and allow stable A1AT to work at its optimum concentration.